Geographical Distribution of South American Tomato Leaf Miner Tuta absoluta (Meyrick, 1917) (Lepidoptera: Gelechiidae) in Nepal - Bajracharya, Ajaya S. R.; Bhat, Binu; Sharma, Prem N. (Journal of the Plant Protection Society, 2018)
South American tomato leaf miner, Tuta absoluta (Meyrick, 1917) (Lepidoptera: Gelechiidae) is an invasive insect pest of tomato (Lycopersicon esculentum Miller) both in field and controlled environment conditions. T. absoluta is native to South America, it was detected first time in Nepal from Kathmandu during May, 2016. Survey was conducted at 46 locations of 31 districts in terai and mid hills of Nepal during February to June 2018. T. absoluta was detected from 45 locations of 30 districts surveyed. T. absoluta which was detected from Kathmandu, Lalitpur, Bhaktapur, Kavre and Dhading districts in 2016 has now been spread into 33 districts across the Nepal. Apart from 33 districts T. absoluta might be present in other districts which were not surveyed during the study. Farmers generally manage T. absoluta through indiscriminate use of chemical pesticides. So, extensive research is needed in future to develop integrated pest management technique which is suitable and sustainable for its management in Nepalese context.